Role of University Department Heads in Providing Feedback to the Teachers - Afshan Naseem (JCTE, 2025)
This study highlights the critical role of leadership in delivering feedback to educators concerning their instructional practices, professional growth, and the research environment. Qualitative research with a phenomenological research design was used to investigate the findings. Utilizing a convenient sampling method, interviews were conducted with three department heads and eleven teachers from the University of the Punjab, Lahore. Separate semistructured interview protocols were created for both heads and teachers. Thematic analysis was applied to derive the findings. The results indicated that feedback from department heads enhances teachers' instructional capabilities, thereby contributing to quality education. Feedback is provided during staff meetings, and individual discussions are held to address specific concerns. Additionally, department heads foster a research-oriented culture among teachers by facilitating participation in seminars, conferences, and international trips. Teachers reported that while feedback on professional development is offered, there are limited resources and avenues for their professional advancement. Some educators noted that their heads create opportunities for networking through seminars, workshops, and conferences. Furthermore, university faculty face constraints in accessing resources necessary for professional excellence. In situations where resources are scarce, it is imperative for heads to ensure equitable access for all teachers and to allocate resources to affiliated instructors in a fair manner.